13. MALNUTRITION STATUS AND SOME ASSOCIATED FACTORS AMONG CHILDREN UNDER 5 YEARS OLD AT VAN GIANG DISTRICT, HUNG YEN PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluation of the prevalence of malnutrition in children under five in Van Giang, Hung Yen province in 2025 and associated factors.Methods: A cross-sectional study was conducted on 600 children under 5 years old and their mothers in 4 communes of Van Giang district, from January to March 2025. Data was collected through anthropometric measurements of children combined with a self-administered questionnaire.Results: The overall rate of malnutrition in children is 19.5%, including 3.2% underweight, 14% stunting, and 5.5% wasting. Child malnutrition is associated with maternal height, maternal weight gain during pregnancy, child's birth weight, and gestational age at birth (p < 0.05). To ensure a healthy pregnancy, it is important for expectant mothers to maintain proper nutrition and attend regular prenatal visits.
Keywords: Malnutrition; children under 5 years old; related factors; Van Giang district